Open Access Citation Advantage: An Annotated Bibliography. - A. Ben Wagner (Issues in Science and Technology Librarianship)
A bibliography on the subject of citations in open access (OA) articles is presented, including the study "Open Access to Scientific Literature: Increasing Citations As An Incentive for Authors to Make Their Publications Freely Accessible," by S. Bernius and M. Hanauske, and the articles "Earlier Web Usage Statistics As Predictors of Later Citation Impact," by T. Brody, S. Harnad, and L. Carr, and "Evolution of Open Access Publishing in Chinese Scientific Journals."